Assessment of Researchers Through Bibliometric Indicators: The Area of Information and Library Science in Spain as a Case Study (2001–2015) - González Alcaide, Gregorio; Gorraiz, Juan Ignacio (Frontiers in Research Metrics and Analytics, 2018)
Research activities are subject to constant processes of evaluation, which increasingly include the use of bibliometric indicators to support decision-making. This paper presents a model for the individual evaluation of different facets of researchers’ work and discusses the interest in using “control” parameters to identify deviations suggesting inappropriate conduct. The proposed model is illustrated through an empirical example that analyzes the activity of Spanish researchers in the area of Library and Information Science. There are important differences among the most productive authors, and in many cases, there is no association between the degree of participation in high-impact journals and citation indicators. The control indicators help to identify behaviors such as excessive self-citation, endogamy with regard to the principal journal of publication, and co-dependence with other investigators. We have identified different roles related to the concept of leadership, measured by means of the participation as first or corresponding author, prestige, direct contribution, active direction, supervision, or management.